Praktik Ekonomi Syariah Dalam Konsep Pemikiran Ziauddin Sardar - Nanda Darojatul Ulya Ma'zum; Fenti Erlinda; Helmi Syaifuddin (FEB Universitas Sultan Ageng Tirtayasa, 2021)
The concept of thought established by Ziauddin Sardar which is seen as a parameter of Islamic scholarship includes; Tawhid (Oneness), Khalifah, Worship, Al-'Ilm (Knowledge), Halal, Haram, Al-'Adl (in this case social justice), Zulm (Tyranny), Istislah (Public Interest), and Diya '(Trash) . By using the concept of thought designed by Ziauddin Sardar, the role of the ten concepts of thought in Sharia-based Economics is re-implemented. This research uses qualitative analysis through literature study, with analytical analysis in the process of summarizing the phenomena the writer observes using scientific logic. and the research results show that Ziauudin Sardar's concept of thought can be implemented in sharia economic practice. So that the results of this study cannot be denied that Ziauddin Sardar's concept of thought has contributed to the practice of Islamic economics, as well as being used as a benchmark for practices and rules that are in line with Islamic law (Alqur'an and Hadith).